Semiotic landscapes of protest and recontextualization of historical memories during the Chilean social uprising (2019-2020) - Cárdenas-Neira, Camila; Pérez-Arredondo, Carolina (Árboles y Rizomas, 2023)
This article addresses the construction of semiotic landscapes around two city squares in the central and southern regions of the country, during the Chilean social uprising that began on October 18, 2019. Drawing on insights from Sociolinguistics and Critical Discourse Studies, it identifies, describes, and exemplifies some processes of protest signage developed in these urban spaces based on a corpus of 125 photographs. The analysis reveals that these landscapes lead to references from historical memory that are linked to the civil-military dictatorship (1973-1990); particularly salient are inscriptions alluding to state repression and subsequent human rights violations perpetrated during the uprising by police and military agents. These inscriptions recontextualize traumatic experiences that permeate both historical periods, such as torture and sexual violence. However, these memories were reinterpreted by current generations with a liberating and combative imprint. They utilized walls as channels for intergenerational communication and the negotiation of interpreting frames about the recent past.
Keywords: semiotic landscapes; protest signage; historical memories; social uprising; Chile